Functional MRI in epilepsy – Comparison of Lateralization index and language scoring - Prabhakar, Anuj; Khandelwal, Niranjan; Vyas, Sameer; Gupta, Vivek; Kharbanda, Parampreet S; Mohanty, Manju (Indian Journal of Radiology and Imaging, 2019)
Aims: To evaluate the role of functional magnetic resonance imaging (fMRI) in epilepsy management and to ascertain whether laterality index (LI) derived from fMRI data, using routinely utilized paradigms, can serve as an adjunct to/or replace preoperative neuropsychological testing for evaluation of language lateralization and impairment. Materials and Methods: This was a prospective study which included 20 consecutive patients with a clinical diagnosis of temporal lobe epilepsy over a period of 1 year. Neuropsychological assessment included oral word association test and animal names test. The scores of both tests were compared with normographic data provided in the NIMHANS neuropsychology battery. Three fMRI paradigms were used, namely, picture naming, word generation, and sentence completion. Processing and statistical analysis were performed subsequently. Results and Conclusion: Right temporal lobe epilepsy (RTLE) was seen in 12 patients and left temporal lobe epilepsy (LTLE) in 8 patients. All patients were right handed. The activation pattern was predominantly left lateralized. Language lateralization varied with the type of paradigm. The overall percentage of patients showing left lateralization ranged from 44.00% for the picture naming task to 75% for the sentence completion. Reduced left lateralization was noted in both LTLE and RTLE patients. A negative correlation was observed in LTLE patients between performance in the verbal fluency and the lateralization index in the temporal and parietal regions of interest (ROI) in the word generation paradigm, suggesting that increased left lateralization was associated with a poorer score on neuropsychological tests. In RTLE patients, however, there was no significant correlation between performance in neuropsychological tests and LI. In conclusion, language lateralization using LI can serve as an adjunct during preoperative evaluation. However, it cannot replace neuropsychological testing.
Keywords: Epilepsy; functional magnetic resonance imaging; language; lateralization